Pesan Moral Dalam Film Bulan Terbelah di Langit Amerika - REZA HERDIANA RESTU; Asep Muhyiddin; Uwes Fatoni (Department of Islamic Communication and Broadcasting, Faculty of Dakwah and Communication, UIN Sunan Gunung Djati Bandung, 2020)
Penelitian ini bertujuan untuk mengetahui makna wacana pesan moral dalam film Bulan Terbelah di Langit Amerika dari segi teks yang terdiri dari struktur makro, superstruktur dan struktur mikro. Penelitian kualitatif ini menggunakan teori analisis wacana model Teun A. Van Dijk untuk mengkaji serta menjelaskan hubungan dan makna wacana pada dimensi teks meliputi struktur makro, superstruktur dan struktur mikro. Berdasarkan hasil penelitian ditemukan tiga kesimpulan utama: Pertama, struktur makro mengenai perbedaan keyakinan bukan sumber dari konflik. Kedua, superstruktur film terdiri dari lima bagian yakni opening sequence, teaser, plotline, climax dan ending. Ketiga, struktur mikro pada bagian film terdapat unsur semantik (latar, detil, maksud) sintaksis (koherensi, bentuk kalimat deduktif-induktif, dan kata ganti) stilistik (bahasa sehari-hari), retoris (grafis, hiperbola, ironi memakai majas hiperbola). Garis besar cerita yang diangkat pada film ini menggunakan pendekatan kontruksi sosial, mengkontruksi wacana mengenai kisah Islam usai tragedy 11/9 di Amerika sebagai pesan moral. This research aims to find out the meaning of the discourse of moral messages in the film Bulan Terbelah di Langit Amerika in terms of text consisting of macro structure, superstructure and micro structure. This qualitative research uses the theory of discourse analysis of the Teun A. Van Dijk that model to study and explain the relationship and meaning of discourse on the dimensions of the text including macro structure, superstructure and micro structure. Based on the results of the study found three main conclusions: first, the macro structure regarding differences in beliefs not the source of conflict. Second, the film superstructure consists of five parts namely opening sequence, teaser, plotline, climax and ending. Third, the micro structure in the film part fulfills the semantic element (background, details, intent) syntactically (coherence, deductive-inductive sentences, and pronouns) stylistic (daily languange) rhetorical (graphic, hyperbole, irony using majas hyperbole). The outline of the story raised in this film uses a social construction approach, constructing a discourse about the story of Islam after the 9/11 tragedy in America as a moral message.